Condition Optimization for the Synthesis of Castor Oil Templated Mesoporous Silica - Shao, Godlisten Namwel; Kimambo, Elianaso Elimbinzi; Pius , Christina Fabian (Tanzania Journal of Engineering and Technology, 2025)
The present work provides suitable conditions for the synthesis of mesoporous materials with improved porosity using an optimization technique. The proposed preparation method involves forming final products by varying the amount of castor oil, media, and template removal. The obtained samples were examined by TGA, XRD, DRIFT and nitrogen physisorption studies. It was observed that the porosity of the obtained samples was dependent on the conditions under which the materials were synthesized. All synthesized materials showed the Type IV adsorption-desorption isotherm features of mesoporous, regardless of the conditions utilized during the synthesis. The sample synthesized using 2.5 g of a castor oil template in acidic media and calcination as a template removal, displayed the highest BET surface area of 906 m2/g, pore volume of 1.44 cm3/g and a pore diameter of 6.5 nm. When reflux was used as a template removal technique on materials synthesized under the same conditions, the surface area was 900 m2/g with a pore volume of 1.4 cm3/g and a pore diameter of 6.6 nm. Even though the latter sample exhibited less surface area, it is still better than the former sample since the template removal by reflux is a greener technique than the removal through calcination. XRD results showed that no peak was observed in low-angle implying that the materials lack long-range order of the pores. This large surface area synthesized mesoporous materials are potential adsorbents or catalytic supports. Therefore, the present study promotes the production of eco-friendly materials using castor oil, a biodegradable and renewable resource, as a pore-directing agent.